Nutritional factors in the prevention and treatment of gout - Sebastian Tomaszuk; Karolina Wąsik; Magda Wojtuś (Nicolaus Copernicus University in Toruń, 2023)
Introduction and purpose: Despite the fact that effective urate lowering therapy and anti-inflammatory drugs for the treatment of gout are commonly available, there is considerable interest in novel treatment approaches. Gouty patients often have a multitude of comorbidities, which lead to concern over drug-drug interactions and medication adverse events. Thus, diet modifications are examined as a way of nonpharmacological treatment of gout. In this review, we explore the potential impact of nutritional factors on hyperuricemia and clinical gout outcomes. A search was conducted using PubMed and Google Scholarship databases. Brief description of the state of knowledge: Management in patients with gout should be holistic. Incorrect nutrition may lead to hyperuricemia. Studies to date suggest that avoidance of certain foods and beverages can decrease the frequency of gout flares. Weight loss may be beneficial for prevention as well as treatment of gout and its comorbidities. The impact of various types of diet on the course of gout has been given particular attention and recent research suggests that vegetarian, mediterranean and dash diets may be beneficial for gouty patients. Also, some vitamins and omega-3 PUFA have favorable effects and the potential clinical use in gout treatment. Conclusions: We propose that simple dietary regimens may be beneficial to complement therapeutic management or contribute to the prevention of flares in gout patients. Although piecemeal modifications of various nutrients often provide incomplete dietary recommendations, understanding the role of nutritional factors in gout development would be helpful for patients in choosing their healthy diet.